TOLERANSI KEKERINGAN BEBERAPA PADI GOGO UNGGUL NASIONAL TERHADAP KETERSEDIAAN AIR YANG TERBATAS - Ahadiyat Yugi Rahayu (Universitas Tadulako, 2012)
Low national productivity of upland rice is due to the limitation of available water especially during dry season. Selection of drought tolerant varieties and high yield production is a suitable solution. The objective of this study was to identify upland rice varieties tolerant to drought and their physiological and morphological characters. The study was carried out in a plastic house at research station of Faculty of Agriculture, General Soedirman University during August to October 2008. A split plot design was used within which fifteen upland rice varieties i.e. Silugonggo, Kalimutu, Gajah mungkur, Dodokan, Way rarem, Jatiluhur, Ciherang, Cisokan, Situ Bagendit, Situ Patenggang, Gilirang, Cirata, Batulegi, Way Ampo Buru and Danau Tempe were the main plots and different water applications i.e. up to the end of vegetative stage, up to the mid of generative stage and up to harvest as sub-plot under Split Plot Design were the sub plots. The result showed that all varieties had no capacity to stand under limited water in different time of water application. Physiological response showed higher values in CGR, RGR and water absorption under water application up to harvest than others. Number of tiller, total leaf area, root dry weight and total root length had similar trend except on plant height.